Chitosan beads as the adsorbent for glyphosate removal from an aqueous solution - Saelim, T; Sairiam, S; Siralertmukul, K; Watcharamul, S; Nuisin, R (Journal of Metals, Materials and Minerals, 2020)
Chitosan beads were prepared to remove glyphosate from an aqueous solution via a batch adsorption system. The optimum conditions, including initial glyphosate concentration, adsorbent dose, and contact time, were investigated. Increasing the initial glyphosate concentration increased the equilibrium adsorption capacity onto the chitosan beads. The rapid sorption of glyphosate was found at an initial contact time of 30 min. The maximum adsorption capacity from 35 mg·L-1 glyphosate in solution onto 0.1 g chitosan beads was 12.7 mg·g-1. Increasing amount chitosan to 0.5 g dosage could remove more than 94% of the glyphosate for all initial glyphosate concentrations (1–35 mg·L-1), pH 7, and room temperature. The pHPZC value of chitosan surface was determined approximately at pH 8.The glyphosate removal by chitosan bead was favored at pH below pHPZC. The effects on the adsorption capacity, adsorption isotherm, and kinetics model were evaluated. The glyphosate uptake behavior fitted with the Freundlich adsorption model, while the kinetic adsorption fitted a pseudo-second order. The adsorption of glyphosate was proposed to be by electrostatic interaction between the negatively charged –PO(OH)- and –COO- groups, and the positively charged –NH3+ groups of chitosan.